PERAN UNITED NATIONS - AFRICAN UNION MISSION IN DARFUR (UNAMID) DALAM PENYELESAIAN KONFLIK KEMANUSIAAN DI DARFUR TAHUN 2016-2020 - Farel Wisnu Anangga, (2022)
This research discusses the role played by the United Nations - African Union In Darfur (UNAMID) which aims to achieve security and peace in the Darfur area. UNAMID itself has a mandate that aims to achieve security stabilization for Darfur. In the course of the UNAMID's term of office ended in 2020 ago, but in reality conflicts are still happening in the Darfur area. Many actions and actions have been taken by UNAMID during its tenure, ranging from humanitarian assistance, mediation and negotiation assistance, to even responding to the Covid-19 issue during the conflict. In this study, the author brings an update in the form of an update on the Darfur situation from 2016-2020. This study aims to see an overview of the Darfur conflict and how the role of the United Nations - African Union Mission In Darfur in carrying out its mandates, which aims to achieve security stabilization in Darfur. The research method used is a qualitative method with a descriptive analysis approach. The author conducted a literature study, namely collecting data from books, articles, journals and the internet. The final result of this research shows that the Darfur conflict is becoming more complex and requires a third party in the resolution process. Also UNAMID has carried out its mandates but in reality the conflict is still continuing.